The information content of dividends on the Johannesburg Stock Exchange: An empirical analysis - L. L. Ooms; A. A. Archer; E. V.D.M. Smit (South African Journal of Business Management, 1987)
The authors attempt to make a contribution to the research into the validity of the efficient market hypothesis on the Johannesburg Stock Exchange by investigating the market's reaction to dividend announcements. Evidence is presented that the efficient market hypothesis is not invalidated as traders on dividend information are not able to generate returns which are significantly different from the return generated by the market portfolio. It seems that the market is not sophisticated enough to distinguish between good and bad news as both portfolios yield either positive or negative abnormal returns. In quite a few cases investors holding a bad news portfolio were better off than holders of a good news portfolio. These facts suggest that the market is probably not reacting to dividend information but to the underlying earnings information which is simultaneously released. These results were obtained by applying the conventional techniques for announcement studies and it is obvious that this methodology should be refined and improved and further adapted to local practices in order to be able to give conclusive answers.
Keywords: 650